RESILIENCE: Phase III Randomized, Double-Blind Trial Comparing Sorafenib With Capecitabine Versus Placebo With Capecitabine in Locally Advanced or Metastatic HER2-Negative Breast Cancer - Baselga, José; Zamagni, Claudio; Gómez, Patricia; Bermejo, Begoña; Nagai, Shigenori E; Melichar, Bohuslav; Chan, Arlene; Mángel, Lászlo; Bergh, Jonas; Costa, Frederico; Gómez, Henry L; Gradishar, William J; et al. (Clinical breast cancer, 2017)
INTRODUCTION: Sorafenib is a multikinase inhibitor with antiangiogenic/antiproliferative activity. In this randomized, double-blind, placebo-controlled phase III trial, we assessed first- or second-line capecitabine with sorafenib or placebo in patients with locally advanced/metastatic HER2-negative breast cancer resistant to a taxane and anthracycline and with known estrogen/progesterone receptor status. PATIENTS AND METHODS: A total of 537 patients were randomized to capecitabine 1000 mg/m2 orally twice per day for days 1 to 14 every 21 days with oral sorafenib 600 mg/d or placebo. The primary end point was progression-free survival (PFS). Patients were stratified according to hormone receptor status, previous chemotherapies for metastatic breast cancer, and geographic region. RESULTS: Treatment with sorafenib with capecitabine, compared with capecitabine with placebo, did not prolong median PFS (5.5 vs. 5.4 months; hazard ratio [HR], 0.973; 95% confidence interval [CI], 0.779-1.217; P = .811) or overall survival (OS; 18.9 vs. 20.3 months; HR, 1.195; 95% CI, 0.943-1.513; P = .140); or enhance overall response rate (ORR; 13.5% vs. 15.5%; P = .515). Any grade toxicities (sorafenib vs. placebo) included palmar-plantar erythrodysesthesia syndrome (PPES; 79.2% vs. 59.6%), diarrhea (47.3% vs. 37.8%), mucosal inflammation (15.4% vs. 6.7%), and hypertension (26.2% vs. 5.6%). Grade 3/4 toxicities included PPES (15.4% vs. 7.1%), diarrhea (4.2% vs. 6.4%), and vomiting (3.5% vs. 0.7%). CONCLUSION: The combination of sorafenib with capecitabine did not improve PFS, OS, or ORR in patients with HER2-negative advanced breast cancer. Rates of Grade 3 toxicities were higher in the sorafenib arm.
Keywords: rozvrh dávkování léků; Capecitabine; Drug Resistance, Neoplasm; Kaplan-Meier Estimate; nádory prsu; hypertenze; Female; placebo; výsledek terapie; ženské pohlaví; Kaplanův-Meierův odhad; antracykliny; přežití bez známek nemoci; přemostěné cyklické sloučeniny; lidé; niacinamid; dvojitá slepá metoda; syndrom ruka-noha; Anthracyclines; Breast Neoplasms; chemorezistence; Drug Administration Schedule; capecitabinum; Treatment Outcome; Taxoids; Antineoplastic Combined Chemotherapy Protocols; Niacinamide; fenylmočovinové sloučeniny; průjem; protokoly protinádorové kombinované chemoterapie; Receptor, ErbB-2; Humans; receptor erbB-2; Hypertension; Double-Blind Method; Aged; Bridged-Ring Compounds; aplikace orální; Diarrhea; Placebos; Disease-Free Survival; lidé středního věku; senioři; Administration, Oral; Phenylurea Compounds; taxoidy; Middle Aged; Hand-Foot Syndrome